Small PNH clones detected by fluorescent aerolysin predict a faster response to immunosuppressive therapy in patients with severe aplastic anaemia. Issue 1 (1st January 2020) - Ren, Xiang; Li, Xingxin; Huo, Jiali; You, Yahong; Huang, Jinbo; Shao, Yingqi; Ge, Meili; Huang, Zhendong; Zhang, Jing; Wang, Min; Jin, Peng; Nie, Neng; et al.
ABSTRACT: Objectives: To clear the obscure conclusion on the prediction value of paroxysmal nocturnal haemoglobinuria (PNH) clones in severe aplastic anaemia (SAA) patients treated with immunosuppressive therapy (IST). Methods: We retrospectively analyzed 219 consecutive SAA patients treated with IST from October 2008 to October 2015 and evaluated the haematological responses to IST. Results: The presence of a PNH clone was detected in 55 (25.1%) patients prior to IST [37/88 by flow cytometry (FCM) and 18/131 by fluorescent aerolysin (FLAER)] and 27 disappeared after IST (23/37 in initial FCM group, 4/18 in initial FLAER group, p = 0.005). In patients without an initial clone, 12 (30.0%) cases in FCM and 17 (19.5%) in FLAER groups presented a PNH clone at least once after IST ( p < 0.001). In patients with a pre-treatment PNH clone detected by FCM, the 3-, 6- and 12-month response rates were higher than patients without ( p = 0.006; 0.002 and 0.002, respectively). And in FLAER group, the 3-month response rate was significantly higher in those with a prior clone ( p = 0.017), however, the 6- and 12-month response rates showed no differences ( p = 0.105, p = 0.144, respectively). By multivariate analysis, a shorter interval between diagnosis and treatment is associated with a better response and survival. Conclusions: A more reliable FLAER method allows us to draw a conclusion that PNH clone predicts a faster response but not a higher response rate to IST. Once a diagnosis is confirmed, the IST should be initiated as soon as possible.